Oral contraceptive use and the clinical course of Crohn's disease: a prospective cohort study. (1st August 1999) - Cosnes, J; Carbonnel, F; Carrat, F; Beaugerie, L; Gendre, J-P
Abstract : BACKGROUND: Women with Crohn's disease are usually advised not to take oral contraceptives, but, unlike smoking, there is no clear association between current oral contraceptive use and more severe disease. AIM: To assess the effect of oral contraceptive use on the clinical course of Crohn's disease. PATIENTS: 331 women, aged 16–50 years, with Crohn's disease and Crohn's disease activity index <200, were enrolled consecutively during a one year period. Patients were classified at inclusion as oral contraceptive users or non-users and smokers or non-smokers. METHODS: A prospective 12–18 month cohort study was used. The main outcome measures were flare up rate and time to flare up. RESULTS: In total, 134 women used oral contraceptives, in most cases low oestrogen formulations. During the study period, 61 oral contraceptive users (46%) developed a flare up, compared with 85 non-users (43%). The hazard ratio for oral contraceptive use was 1.11 (95% confidence interval 0.80 to 1.55). Variables associated with flare up were smoking status, recently active disease, baseline Crohn's disease activity index, and presence of anoperineal lesions. The same results were obtained when the analysis was restricted to patients eligible for a relapse prevention trial. CONCLUSION: Unlike smoking, oral contraceptives have no effect on Crohn's disease activity.